The United States Geostrategic and Economic Interests in the Middle East and Arab-Israeli - Oyekanmi, Abdullahi Abiodun; Olayinka, Iseoluwa Raphael; Omojowo, Sunday Toyin; Salako, Samuel Anuoluwapo (Journal of Contemporary International Relations and Diplomacy, 2024)
The Arab-Israeli conflict is a paradigm shift from other global conflicts, partly due to its protracted nature and the inherent influence of third-party states like the United States and the erstwhile Soviet Union in the Middle East crisis. The paper is projected to review the unabated Arab-Israeli conflicts and the United States expressed geo-political and economic interests in the Middle East. Thus, the paper adopted the desk research method and third-party intervention theory as explanatory frameworks. It was discovered that the protracted Arab-Israeli crisis festered on because of the desire of the United States to use Israeli forces to curtail Arab civilization from challenging Western culture and ensure access to the oil in the Middle East. This was made possible due to inability of the United Nations to enforce its resolutions. These became harbingers of troubles in the Middle East, hence Arab-Israeli conflict became a continuum. In effect, the unity of the Arab world, a review of United States arms and financial supports to Israel and a more functional United Nations to de-radicalize relationships in the Middle East are recommended as possible solutions.